Adreno‐muscarinic synergy in the male human urinary outflow tract. Issue 7 (20th April 2018) - Walther, Sebastian; Strittmatter, Frank; Hennenberg, Martin; Gratzke, Christian; Stief, Christian G.; Roosen, Alexander
Abstract : Aim: To examine putative interaction between adrenergic and muscarinic contractile activation in the human urinary outflow tract. Methods: Tissue from the trigone and prostatic urethra was obtained from 12 cystectomy and 16 prostatectomy specimen. Contractions were elicited by exposure to exogenous agonists before and after inhibition of Rho kinase and protein kinase c (PKC). Immunofluorescence and Western‐blot studies were performed using antibodies to muscarinic M3‐receptors (M3‐R) and alpha1A‐adrenoreceptors (alpha1A‐AR). The study is registered withClinicalTrials.gov, number NCT01227447. Results: There was strong co‐localization of M3‐R and alpha1A‐AR on trigonal and urethral myocytes. Western blot analysis revealed a significantly higher expression of alpha1A‐AR in the superficial than in the deep trigone. Phenylephrine (PE, 1 μm) augmented contractions induced by carbachol (CA, 3 μm) to more than threefold control in the male superficial trigone, and to about sevenfold control in the proximal urethra. No such potentiation could be detected in female bladder outlet. Both PKC inhibitor GF 109203X and Rho kinase inhibitor Y‐27632 reduced responses to 1 μM PE as well as to 3 μM CA significantly. However, the synergistic effect of the combined intervention remained proportionally unaffected. Conclusions: Muscarinic and adrenergic receptor activation exerts a strong synergistic effect in the male human bladder trigone and proximal urethra.